1987
DOI: 10.1152/ajpendo.1987.253.2.e214
|View full text |Cite
|
Sign up to set email alerts
|

Heat production during contraction in skeletal muscle of hypothyroid mice

Abstract: The effect of hypothyroidism on tension-independent and -dependent heat produced during a twitch and a tetanic contraction of extensor digitorum longus (EDL) and soleus muscle of mice was examined. The amount of heat produced during a twitch and the rate of heat development during a tetanus of EDL and soleus were measured at and above optimal length. The effect of hypothyroidism on force production was less than 30%. Straight lines were used to fit the relation between heat production and force. Hypothyroidism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…UCP3 activators FFAs and ROS accumulate in SKM during contraction or exercise (Watt et al, 2003;McArdle et al, 2004), and Curtin et al (2002) found that SKM UCP3 overexpression enhances the thermogenic response to contraction ex vivo, but no differences in muscle temperatures were apparent at rest. Likewise, for any given amount of mechanical work, EU SKM generates more heat than HYPO (Leijendekker et al, 1987). This increased thermogenesis probably results from activation of an UCP because compared with EU; SKM mitochondria from HYPER rats exhibit increased proton conductance (Brand et al, 1992) along with increased levels of ROS (Gredilla et al, 2001), FFAs (Lombardi et al, 2002), and coenzyme Q, a putative cofactor for UCP activity (Venditti et al, 2003).…”
Section: Determinants Of Sympathomimetic-induced Hyperthermia 277mentioning
confidence: 99%
“…UCP3 activators FFAs and ROS accumulate in SKM during contraction or exercise (Watt et al, 2003;McArdle et al, 2004), and Curtin et al (2002) found that SKM UCP3 overexpression enhances the thermogenic response to contraction ex vivo, but no differences in muscle temperatures were apparent at rest. Likewise, for any given amount of mechanical work, EU SKM generates more heat than HYPO (Leijendekker et al, 1987). This increased thermogenesis probably results from activation of an UCP because compared with EU; SKM mitochondria from HYPER rats exhibit increased proton conductance (Brand et al, 1992) along with increased levels of ROS (Gredilla et al, 2001), FFAs (Lombardi et al, 2002), and coenzyme Q, a putative cofactor for UCP activity (Venditti et al, 2003).…”
Section: Determinants Of Sympathomimetic-induced Hyperthermia 277mentioning
confidence: 99%
“…At the end of experiments, the length of fibre bundles was measured, tendons were removed and muscles were dried for at least 24 h. Dry weight was measured using an electronic balance (Cahn 25, Cahn Instruments, Cerritos, CA, USA). To allow comparison with previous results, wet weight was estimated assuming a wet/dry weight ratio of 5*0 (Leijendekker, Hardeveld & Elzinga, 1987).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Not only TH increases the number of energy transformations, as evidenced by 30À50% reduced minimal energy cost of living and reflected by BMR or resting energy expenditure (REE) in hypothyroidism, but it also reduces the thermodynamic efficiency of the homeothermic machine for the sake of producing more heat. For example, for any amount of mechanical work, euthyroid rat muscles generate more heat than the hypothyroid counterpart (Leijendekker et al, 1987). Likewise, the energy cost of producing a given amount of glycogen from lactate is higher in euthyroid than hypothyroid hepatocytes (Berry et al, 1989).…”
Section: Thyroid Hormone (Th) Thermogenesis and Temperature Homeostasismentioning
confidence: 99%